x-y=-2

Subtract x from both sides of the equation.

-y=-2-x

Multiply each term in -y=-2-x by -1

Multiply each term in -y=-2-x by -1.

(-y)⋅-1=(-2)⋅-1+(-x)⋅-1

Multiply (-y)⋅-1.

Multiply -1 by -1.

1y=(-2)⋅-1+(-x)⋅-1

Multiply y by 1.

y=(-2)⋅-1+(-x)⋅-1

y=(-2)⋅-1+(-x)⋅-1

Simplify each term.

Multiply -2 by -1.

y=2+(-x)⋅-1

Multiply (-x)⋅-1.

Multiply -1 by -1.

y=2+1x

Multiply x by 1.

y=2+x

y=2+x

y=2+x

y=2+x

y=2+x

Choose any value for x that is in the domain to plug into the equation.

Remove parentheses.

y=2+0

Add 2 and 0.

y=2

Use the x and y values to form the ordered pair.

(0,2)

(0,2)

Remove parentheses.

y=2+1

Add 2 and 1.

y=3

Use the x and y values to form the ordered pair.

(1,3)

(1,3)

Remove parentheses.

y=2+2

Add 2 and 2.

y=4

Use the x and y values to form the ordered pair.

(2,4)

(2,4)

These are three possible solutions to the equation.

(0,2),(1,3),(2,4)

Find Three Ordered Pair Solutions x-y=-2